METHODS FOR TABULAR IMPLEMENTATION OF ARITHMETIC OPERATIONS OF THE RESIDUES OF TWO NUMBERS REPRESENTED IN THE SYSTEM OF RESIDUAL CLASSES - Krasnobayev, V. A.; Yanko, A. S.; Kovalchuk, D. M. (Radio Electronics, Computer Science, Control, 2022)
Context. Implementation of modular arithmetic operations of addition, subtraction and multiplication by a tabular method based on the use of the tabular multiplication code. The object of the study is the process of tabular implementation of basic arithmetic operations on the residues of numbers represented in the system of residual classes. Objective. The goal of the work is to develop methods for the tabular implementation of the arithmetic operations of multiplication, addition and subtraction of the residues of two numbers based on the use of the tabular multiplication code. Method. Tabular methods for implementing integer arithmetic modular operations of addition, subtraction and multiplication are proposed for consideration. In order to reduce the amount of equipment for a tabular operating unit of computer systems that implements modular operations of addition, subtraction and multiplication by reducing the coincidence circuits AND in the nodes of the tables for implementing arithmetic operations based on the code of table multiplication, two methods for performing arithmetic modular operations of addition and subtraction have been developed. These methods are based on the code of tabular multiplication, the use of which will reduce the amount of equipment of the tabular operating unit. Thus, despite the difference in the digital structure of the tables of modular operations of addition, subtraction and multiplication based on the use of the tabular multiplication code, two new tabular methods for implementing arithmetic modular operations of addition and subtraction have been created. Based on them, algorithms for tabular execution of modular arithmetic operations of addition and subtraction have been developed. Using these algorithms, it is possible to synthesize a structurally simple, highly reliable and fast table operating unit that operates in a system of residual classes, which is based on three separate permanent storage devices (read-only memory), each of which implements only one fourth of the corresponding complete table of values of the modular operation, what is earlier in the theory tabular arithmetic was supposed to be impossible. Results. The developed methods are justified theoretically and studied when performing arithmetic modular operations of addition, subtraction and multiplication using tabular procedures. Conclusions. The conducted examples of the implementation of integer arithmetic modular operations of addition and subtraction can be considered as presented experiments. The results obtained make it possible to recommend them for use in practice in the design of computer systems operating in a non-positional number system in residual classes. Prospects for further research may be to create a tabular method for implementing integer arithmetic modular division operations based on the use of the tabular multiplication code.